(untitled) (Torani Journal of Fisheries and Marine Science, 2023)
Catfish is a popular freshwater fish and is in great demand as a consumption fish because catfish meat has a delicious taste and is quite high in calories and protein. Catfish skin as a by-product of fillet production can be used as raw material for processing chips. This research aims to determine the effect of soaking ingredients on the physical and chemical characteristics of catfish skin chips. This research was carried out by making catfish skin chips through the process of first washing, first soaking with soaking materials, second washing, second soaking in spices, drying, cutting, frying, and packed. The treatment in this research is the soaking material (in the first soaking) used. There were 4 treatments with different soaking ingredients, including: P0 (control), P1 (lime), P2 (acetic acid/vinegar), and P3 (palm vinegar). After the skin chips with the 4 treatments have been produced, quality testing is carried out on the product. Tests were carried out on yield, consumer acceptability through hedonic testing, physical characteristics of skin chips through analysis of crispness, efflorescence and oil absorption, chemical characteristics through proximate analysis, and microbial contamination through ALT analysis. Treatment P1 is known to have the highest yield, crispness, oil absorption capacity, and efflorescence ability among other treatments. Next, the products tested for chemical content are selected based on the treatment that obtains the highest level of consumer acceptance. Based on hedonic testing, it is known that P1 is the treatment most sought after by consumers. From the results of the chemical analysis that has been carried out, the ash content and protein content of fish skin chips in P1 is higher than P0, but has a lower water content than P0. The Total Plate Number (ALT) value for each catfish skin chips parameter exceeds the standard limit of SNI 7388:2009, namely 5x105 CFU/g.